Efficacy of Various Estrus Synchronization Protocols in Improving Conception Rate in Surti Goats - Parmar, Chirag P; Patel, Jagdish A; Manzarul Islam, Md; Dhami, Arjan J; Patel, Ashish C (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The objective of the study was to compare the efficacy of three different estrus synchronization protocols for estrus induction/synchronization and conception rate in Surti does. Forty adult non-pregnant Surti goats were selected and equally divided based on serum progesterone levels into four groups (n=10 each), viz., Group-1: Intravaginal sponge protocol with natural service by intact buck after sponge removal, Group-II: Double PGF2α injection protocol (11 days apart) with natural service within 48 to 144 h after 2nd PG injection, and Group-III: Ovsynch protocol with natural service after 2nd GnRH injection, and Group-IV: was kept as untreated control. Goats having progesterone level ≤0.8 ng/mL and ≥1.4 ng/mL was kept in Group-I and III, and in Group-II, respectively. The estrus response was found 100% in the goats kept under each treatment group and 30% in control during study period of two months. Estrus induction intervals from last PGF2α injection were statistically similar in all treatment protocols. Significantly (p<0.05) shorter estrus duration was observed in ovsynch as compared to intravaginal sponge and double PGF2α injection protocols. Conception rates in Group I, II and III at induced estrus were 60, 80 and 40, and overall of 3 cycles 100, 100 and 80 %, respectively. In control Group-IV, out of 3 goats exhibited estrus, 1 conceived at first estrus and 1 in 2nd cycle. Thus, double PG treatment protocol (Gr-II) appeared the best, followed by vaginal sponge (Gr-I) in terms of conception rate at induced estrus (80 vs. 60%), and overall of 3 cycles (100 vs. 100%) over Ovsynch protocol (Gr-III), and untreated control goats.